In Situ Simulated Cardiac Arrest Exercises to Detect System Vulnerabilities. Issue 3 (June 2015) - Barbeito, Atilio; Bonifacio, Alberto; Holtschneider, Mary; Segall, Noa; Schroeder, Rebecca; Mark, Jonathan
<x xml:space="preserve">Abstract</x> Introduction Sudden cardiac arrest is the leading cause of death in the United States. Despite new therapies, progress in this area has been slow, and outcomes remain poor even in the hospital setting, where providers, drugs, and devices are readily available. This is partly attributed to the quality of resuscitation, which is an important determinant of survival for patients who experience cardiac arrest. Systems problems, such as deficiencies in the physical space or equipment design, hospital-level policies, work culture, and poor leadership and teamwork, are now known to contribute significantly to the quality of resuscitation provided. Methods We describe an in situ simulation-based quality improvement program that was designed to continuously monitor the cardiac arrest response process for hazards and defects and to detect opportunities for system optimization. Results A total of 72 simulated unannounced cardiac arrest exercises were conducted between October 2010 and September 2013 at various locations throughout our medical center and at different times of the day. We detected several environmental, human-machine interface, culture, and policy hazards and defects. We used the Systems Engineering Initiative for Patient Safety (SEIPS) model to understand the structure, processes, and outcomes related to the hospital's emergency response system. Multidisciplinary solutions were crafted for each of the hazards detected, and the simulation program was used to iteratively test the redesigned processes before implementation in real clinical settings. Conclusions We describe an ongoing program that uses in situ simulation to identify and mitigate latent hazards and defects in the hospital emergency response system. The SEIPS model provides a framework for describing and analyzing the structure, processes, and outcomes related to these events.